2014
DOI: 10.1371/journal.pone.0091139
|View full text |Cite
|
Sign up to set email alerts
|

Co-Expression of HER Family Members in Patients with Dukes’ C and D Colon Cancer and Their Impacts on Patient Prognosis and Survival

Abstract: The human epidermal growth factor receptor (EGFR) is an important therapeutic target in patients with metastatic colorectal cancer and anti-EGFR antibodies cetuximab and panitumumab have been approved for the treatment of such patients. Despite these advances, the duration of response in some patients can be limited. Since, EGFR is capable of forming heterodimers with the other members of the HER (Human epidermal receptor) family, it is important to investigate the co-expression and prognostic significance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…Cetuximab is a chimeric human-murine monoclonal IgG1 antibody that binds to the extracellular domain of EGFR and inhibits ligand binding, dimerization and ultimately its activation. Cetuximab has shown efficacy in treating HNSCC, mCRC and NSCLC however, several clinical studies have shown that intrinsic and acquired resistances are common (27)(28)(29)(30)(31)(32). Determining why tumors are initially resistant to cetuximab or develop resistance during the course of therapy represents a major clinical challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Cetuximab is a chimeric human-murine monoclonal IgG1 antibody that binds to the extracellular domain of EGFR and inhibits ligand binding, dimerization and ultimately its activation. Cetuximab has shown efficacy in treating HNSCC, mCRC and NSCLC however, several clinical studies have shown that intrinsic and acquired resistances are common (27)(28)(29)(30)(31)(32). Determining why tumors are initially resistant to cetuximab or develop resistance during the course of therapy represents a major clinical challenge.…”
Section: Discussionmentioning
confidence: 99%
“…EGFR signaling can involve a number of intracellular molecules such as extracellular signal-regulated kinase (ERK), cyclin D1 and β-catenin [51]. The presence of EGFR is detected in a wide range of cancer types (Table 3 [51], [52], [53], [54], [55], [56], [57], [58], [59], [60], [61], [62], [63], [64], [65], [66], [67], [68], [69], [70], [71], [72], [73], [74], [75], [76], [77]). Normally, the EGFR gene is located on chromosome 7.…”
Section: The Egfr and Its Familymentioning
confidence: 99%
“…Head and neck Up to 90% Rarely detectable (Grandis and Tweardy, 1993;Hanken et al, 2014) Non-small cell lung carcinoma 34-62% 16-35% (Hirsch et al, 2003;Hirsch et al, 2002;Brabender et al, 2001) Colorectal 43-80% 6-77% (Spano et al, 2005;Seo et al, 2014;Khelwatty et al, 2014) Breast 6-18% 20-30% (Sorlie et al, 2001;Slamon et al, 1987;Rimawi et al, 2010;van, V et al, 1988;Bhargava et al, 2005;Lazaridis et al, 2014) Ovarian 48-62% 11-40% (Verri et al, 2005;Tuefferd et al, 2007;Nielsen et al, 2004;Lafky et al, 2008) Pancreatic 42-69% 61% (Uegaki et al, 1997;Tobita et al, 2003;Bloomston et al, 2006;Komoto et al, 2009) Glioma 40-50% Rarely detectable (Shinojima et al, 2003;Faulkner et al, 2014;Haynik et al, 2007) Cervical 33-73% 19-42% (Kim et al, 1996;Oka et al, 1994;Tangjitgamol et al, 2005) It was originally thought that EGFR amplification promoted tumor growth exclusively by enhancing signaling through wild-type EGFR. Since then, several EGFR mutations in both the intracellular and extracellular domain have been identified as predictors for response to EGFR-targeted therapies (Sok et al, 2006;Kobayashi et al, 2005).…”
Section: Tumors Overexpressing References Egfr Her2mentioning
confidence: 99%